Influence of Water Stress on Morphology, Physiology and Yield Contributing Characteristics of Rice (SAARC Journal of Agriculture, 2020)
Water stress or drought is one of the main reasons behind the lower productivity of rice–a widely popular nutritious cereal crop and the staple food for a large portion of the world’s population. A pot experiment was conducted to investigate the effect of water stress on three rice varieties e.g. Banglamoti, Vittiatash and Atash balam in a silty clay soil. To identify whether less water affects rice production, rice plants were cultivated under five different water treatments, T1: flooding at 5 cm depth, T2: flooding at 3 cm depth, T3: saturated water condition, T4: water content@75% saturation, and T5: water content @50% saturation, and were arranged in a completely randomized design with three replications. Morphology, yield and physiological parameters of the rice plants were evaluated. Treatment below saturation did not produce any yield for all the rice varieties studied. All the morphological parameters and yields (e.g. dry weight of plants, plant height, tiller number, panicle number, grain number, grain weight, 1000 seed weight, and harvest index) showed a lower value under water deficient condition. Relative water content and water use efficiency declined with declining water content which represented the variations in their physiological responses to water stress. The grain content per panicle as well as 1000 grain weight of the rice varieties was maximum at saturation condition. Highest harvest index was observed for Vittiatash rice variety at saturated condition. Flooding the soil with either 5 cm or 3 cm depth did not produce any significant change in the studied parameters which indicated that approximately 2 cm water can easily be curtailed which may not affect the production of rice.SAARC J. Agri., 18(1): 61-71 (2020)